Pencegahan Plebitis dengan Assesment Skor Diva dalam Intervensi Bundle Adult - Hastuti, Eka Puji; Armiyati, Yunia; Soesanto, Edy (Universitas Malahayati, 2025)
ABSTRACT Peripheral intravenous catheters (PIVC) are the most commonly used invasive medical devices in healthcare with an overall failure rate of 35-50%. The aim of this literature review is to increase awareness that infections caused by PIVC are a relevant problem that can be reduced by changes in practice Research Method: literature review by searching articles on the Scopus, Science Direct, Pubmed, Google Scholar databases between 2019-2024 using the PRISMA method The keywords used are phlebitis and Bundle Adult and Diva Score. Article searches found 10 sources that met the inclusion criteria. Results: Criteria for inclusion in the search. Sources of this literature include: articles that examine the prevention of phlebitis by assessing DIVA scores in interns, articles available in English or Indonesian, articles available in full text form, articles published in 2019-2023, and in the form of research articles/original articles. The research articles reviewed by researchers are briefly explained. The conclusion of this literature review is nursing interventions that can be used in practice to prevent complications of PIVC installation. Keywords: Phlebitis And Bundle Adult and Diva Score ABSTRAK Kateter intravena perifer (PIVC) merupakan perangkat medis invasif yang paling umum digunakan dalam layanan kesehatan dengan tingkat kegagalan keseluruhan 35-50%. Tujuan dari literatur review ini untuk meningkatkan kesadaran bahwa infeksi yang disebabkan oleh PIVC merupakan masalah relevan yang dapat dikurangi dengan perubahan praktik Metode Penelitian: literature review dengan menelusuri artikel pada database Scopus, Scince Direct, Pubmed, Google Scholar antara tahun 2019-2024 dengan metode PRISMA. Kata kunci yang digunakan yaitu plebitis dan Bundle Adult dan Diva Score. Penelusuran artikel didapatkan 10 sumber yang sesuai dengan kriteria inklusi. Hasil: Kriteria Penyertaan dalam pencarian Sumber literatur ini antara lain: artikel yang mengkaji tentang pencegahan plebitis dengan assesment skor diva dalam internsi, artikel tersedia dalam bahasa Inggris atau Indonesia, artikel tersedia dalam bentuk full text, artikel terbitan tahun 2019-2023, dan dalam bentuk artikel penelitian/artikel asli. Artikel penelitian yang direview peneliti dijelaskan secara singkat Kesimpulan simpulan pada literatur review ini adalah intervensi keperawatan yang dapat digunakan dalam praktek untuk mencegah komplikasi pemasangan PIVC Kata Kunci: Plebitis and Bundle Adult and Diva Score